Plan de negocio para la importación y comercialización de cascos marca Airoh desde Italia - Sacheri Solorzano, Bruno (2017)
The present titling work aims to determine the feasibility of implementing an importer and marketer company of Airoh helmets from Italy since the market would be willing to buy the product. The target market that is intended to arrive through the products offered by Airoh under the company Euro Equipment is directed towards people who practice extreme sports such as motocross, quadcross, enduro among other sports related to this discipline. Imports of helmets in Ecuador are inevitable because the country does not currently have companies producing motorcycle helmets. The study methodology for this project was based on the analysis of the environment to which it is intended to have a clearer picture about potential customers and their purchasing habits. Strategies were used to support an adequate marketing plan that allows the best introduction of the product in the Ecuadorian market. The company will be incorporated as a limited company under the name of Euro Equipment LTD, proposing a mixed capital structure. The investment will be USD 75,011.28 with 30 percent equity and 70 percent capital financed by Banco del Pichincha. The financial evaluation was carried out with a five-year projection where positive indicators were obtained that confirm the viability of the project for both the company and the investors. Likewise, within five years the investment needed to start the project will be recovered.